The Abundance of Plankton in Fish Breeding Basin African Catfish (Clarias gariepinus) With the Frequency of Inoculant Bactreria in Engineering Biofloc - Sukma, Riri Annisa; Pamukas, Niken Ayu; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted 17 juny to 16 july 2015 held at environmental quality laboratory cultivationand fish farming technology in order to determine the frequency of bacterial inoculants on pisciculture tub African catfish (Pangasius gariepinus) in promoting the development of plankton abundance with biofloc techniques. The method used in this research is experiment by using completely randomized design (CRD) 1 factor, 5 level treatments and 3 replications. The peak of plankton abundance on all treatments occurred on day 6, 14, and 22. The classes are Chlorophyta, Cyanophyta, Bacillariophyta, Xantophyta, Protozoa dan Rotatoria. The best average abundance of plankton is found in the frequency of bacterial inoculants 6 times every 5 days as many as 12,640 ind/L. It is supported by parameter of water quality in each treatmant where water quality consist of: temperatur 27-32 0C, pH 6,6-7,2, DO 2,39-4,80 mg/L, C02 3,99-18,11 mg/L, amonia 0,0005-0,0322 mg/L, turbidity 0,12-31 NTU, nitrate 0,12-8,04 mg/L, phosphate 0,13-1,18 mg/L and organic materials 13,90-26,99 mg/L respectivelyKey Words: biofloc, plankton, water quality.